Mobility support in MPLS network - Mahmoud, Omer; Khalifa, Othman Omran; Sellami, Ali; Hassan Abdalla Hashim, Aisha; Saeed, Rashid Abdelhaleem (2011)
Multi Protocol Label Switching (MPLS) is a core networking Quality of service architecture that basically operates in between Layers 2 and 3 of the Open Systems Interconnection (OSI) model; for this reason, MPLS has been referred to as operating at Layer 2.5. MPLS provides its users a number of advantageous features for instance guarantee Quality of Service (QoS), failure protection,. MPLS networks along with Traffic engineering enable load balancing all over the network by explicitly mapping the traffics into TE tunnel that use pre-specified route, which may be not shorted path, MPLS protocol was developed without having mobility in mind. MPLS features and benefits could be extended to support Mobile Nodes. This paper presents study of handover in MPLS domain. It suggests utilizing Bandwidth Agent to coordinate and facilitate the handover. Two scenarios were considered hard handover and soft handover. Simulation result shows that soft handover lead to smooth transition with less delay and losses.